2015
DOI: 10.3389/fsurg.2015.00023
|View full text |Cite
|
Sign up to set email alerts
|

Endometriosis and Vesico-Sphincteral Disorders

Abstract: ObjectivesThe aim of this mini review is to determine the relationship between endometriosis and urinary tract symptoms and to investigate the consequences of surgical treatment of mild to severe endometriosis, especially deep lesions, on the vesico-sphincteral function (lower urinary tract function).Materials and methodsWe performed a literature review by searching the MEDLINE database for articles published between 2000 and 2014, limiting the searches to the words: urinary tract, vesico-sphincteral, dysfunct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 27 publications
(57 reference statements)
0
16
0
Order By: Relevance
“…Nevertheless,impactofDIEsurgeryonsexualfunctionis poorlyreportedinthemostimportantsurgicalseries(71)and datashowcontradictingresults.VandenBroecketalin2013 showedinaprospectivestudy,that63patientswhounderwentextensivesurgery(CO 2 laser)withbowelresectionfor moderateandsevereendometriosis,experiencedbetterorat leastsimilarimprovementsinsexualfunctioningthanthose whounderwentsurgerywithoutbowelresection (86).More recently,DiDonatoetal(87)foundasignificantimprovement betweenpre-andpost-surgicaltreatmentinthescoresofthe satisfaction scale, desire scale and pelvic problem interfer-encescaleofSexualHealthOutcomesinWomenQuestionnaire(SHOW-Q)in250patientswhounderwentlaparoscopic DIEexcision.Independentlytothepost-operativereduction in levels of dyspareunia, that undoubtedly influenced the otherdomainsofsexualfunctioning(desire,arousalandorgasm), and considering that appropriate assessment tools anddesignstudyaredifficulttosetup,laparoscopicDIEexcisionbyitself,seemstoamelioratethesexualfunction.Similar findingshavebeenreportedinseveralstudies (88)(89)(90),while earlierstatementsdescribedsexualdisturbancessuchasanorgasmia after low rectum resection due to damage of the autonomicnervesinfemalepatientswithrectalcancer (91). Moreover, a few studies had demonstrated significant presurgicalbladderdysfunctioninwomenaffectedbyposterior DIE (51,53,92,93), probably due to the neurotropism expressedbytheendometrioticcellsandthefibroticneuronal visceralinvasion (5,(94)(95)(96).However,theincidenceofvesicosphincteral symptoms in DIE seems to be under-estimated becauseofalackofuseofpre-surgicalspecificquestionnaire andurodynamicevaluation (97).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless,impactofDIEsurgeryonsexualfunctionis poorlyreportedinthemostimportantsurgicalseries(71)and datashowcontradictingresults.VandenBroecketalin2013 showedinaprospectivestudy,that63patientswhounderwentextensivesurgery(CO 2 laser)withbowelresectionfor moderateandsevereendometriosis,experiencedbetterorat leastsimilarimprovementsinsexualfunctioningthanthose whounderwentsurgerywithoutbowelresection (86).More recently,DiDonatoetal(87)foundasignificantimprovement betweenpre-andpost-surgicaltreatmentinthescoresofthe satisfaction scale, desire scale and pelvic problem interfer-encescaleofSexualHealthOutcomesinWomenQuestionnaire(SHOW-Q)in250patientswhounderwentlaparoscopic DIEexcision.Independentlytothepost-operativereduction in levels of dyspareunia, that undoubtedly influenced the otherdomainsofsexualfunctioning(desire,arousalandorgasm), and considering that appropriate assessment tools anddesignstudyaredifficulttosetup,laparoscopicDIEexcisionbyitself,seemstoamelioratethesexualfunction.Similar findingshavebeenreportedinseveralstudies (88)(89)(90),while earlierstatementsdescribedsexualdisturbancessuchasanorgasmia after low rectum resection due to damage of the autonomicnervesinfemalepatientswithrectalcancer (91). Moreover, a few studies had demonstrated significant presurgicalbladderdysfunctioninwomenaffectedbyposterior DIE (51,53,92,93), probably due to the neurotropism expressedbytheendometrioticcellsandthefibroticneuronal visceralinvasion (5,(94)(95)(96).However,theincidenceofvesicosphincteral symptoms in DIE seems to be under-estimated becauseofalackofuseofpre-surgicalspecificquestionnaire andurodynamicevaluation (97).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the classical pain syndrome of DIE (characterized by dysmenorrhea, dyspareunia, chronic pelvic pain, dysuria and dyschezia), deep lesions are associated with dysfunction of the pelvic organs and pelvic floor muscle (PFM). A series of events or combination of factors may contribute to the development of non‐relaxing PFM disorder in women with chronic pelvic pain, including direct or indirect (neuropathic) injury to the pelvic floor muscle, pelvic pain symptoms and inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…The main clinical manifestations of endometriosis are peritoneal endometriosis, endometriotic ovarian cysts and deeply infiltrating endometriosis (DIE) (2). The latter is considered the most aggressive form of endometriosis, characterized by an infiltration of more than 5 mm (5, 6). DIE affects about 20% of women with endometriosis and causes pelvic pain and poor quality of life (6).…”
mentioning
confidence: 99%